Effectiveness of using Technology Supportive Materials for Developing Listening Skills among School Children - SULTUNA, YEASMIN (THE PRIMARY TEACHER, 2015)
Listening occupies a central place in everyday communication, as most of our knowledge of the world is derived from listening inputs. In spite of the centrality of listening, it has received an unfair treatment in second and foreign language classrooms. The present paper discusses why it is imperative to develop listening skills among learners. Besides, this paper aimed to study the effectiveness of using technology supportive materials for developing listening skills in English among school students. Two group pre-test post-test design was followed in the study. The experiment was conducted for thirty days. Students of two sections of Class VIII constituted the sample group. Analysis of the data was done using both descriptive and inferential statistics. It is found that the use of Technology Supportive Materials is more effective than traditional method for developing listening skills in English among school students.